Lack of regional specificity for connections formed between thalamus and cortex in coculture. - Molnár, Z; Blakemore, C (1991)
The mammalian cerebral cortex consists of many structurally and functionally specialized areas, with characteristic input from particular nuclei of the thalamus. Some localized external influence, such as the arrival of fibres from the appropriate thalamic nucleus before or around the time of birth, could trigger the emergence of committed cortical fields from an undifferentiated 'protocortex. The guidance of axons from each thalamic nucleus to its appropriate target area in the cortex could, then, be crucial in the regulation of cortical differentiation. Recently, Yamamoto et al. and Bolz et al. have demonstrated that cocultured explants of rat lateral geniculate nucleus and visual cortex can form layer-specific interconnections. We have now tested the possibility that each cortical area exerts a selective trophic influence on axons from its appropriate thalamic nucleus, and vice versa, by coculturing explants of different regions of the thalamus and cortex taken at various stages of development. Although thalamo-cortical and cortico-thalamic connections formed in vitro can be remarkably normal in many respects, they lack regional specificity.